Trophic Status of the Solok Pulau Lake, Tanjung Balam Village, Siak Hulu Sub-district Kampar District Riau Province Based on Nitrate and Phosphate Concentration - Nababan, Rodo Sinatra; Simarmata, Asmika Harnalin; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Nitrate and Phosphate concentration is related to fertility of the water andthus as a basis determine the trophic status of the waters. A research aims tounderstand the trophical status of the waters of the Solok Pulau lake, an oxbowlake located in the Tanjung Balam Village, was conducted in January-Febuary2015. A purposive sampling method was applied for taking the water sample.There were 4 stations, namely St 1 (in the inlet from the Kampar River), St 2 (inthe middle of the lake), St3 (in the lake inlet from the Tangon River) and St 4 (inthe distanct part of the lake). Samplings were conducted 3 times, once/ week.Water samples were taken from the surface.Results shown that the nitrate concentration was ranged from 0.082 -0.159 mg/L and phosphate 0.023 - 0.033 mg/L, temperature 28 - 29Â°C,transparency 46 - 53 cm, depth 147 - 297 cm, current speed 3 - 15 cm/s, pH 5.5,dissolved oxygen (DO) 1.29 â 2.17 mg/L. Based on nitrate concentration, thetrophic status of the Solok Pulau Lake was oligotrophic, while based onphosphate concentration, it can be categorized as mesotrophic.Keyword: trophic status, nitrate, phosphate, Solok Pulau lake, oxbow lake